Depression Screening in Diabetes Care to Improve Outcomes: Are We Meeting the Challenge?. (October 2016) - Barnacle, Mykell; Strand, Mark A.; Werremeyer, Amy; Maack, Brody; Petry, Natasha
Purpose: Evidence-based guidelines recommend regular depression screening among individuals with type 2 diabetes mellitus (T2DM). The purpose of this study is to examine depression screening patterns among a primary care population with T2DM, through use of the Patient Health Questionnaire-9 (PHQ-9). Methods: In total, 1817 patients with T2DM were analyzed through a retrospective observational study at 2 sites, a regional health center and a federally qualified health center (FQHC). The T2DM sample was divided into those with and without a major depressive disorder (MDD) diagnosis. Depression screening rates and depression severity were assessed through the PHQ-9. Results: Both sites had higher rates of PHQ-9 screening among individuals with a history of MDD (64.82%) vs those without MDD (11.39%). Individuals from the FQHC without a history of depression had a higher mean PHQ-9 score (10.11) than those with a previous MDD diagnosis at both RHS and FQHC (7.16 and 9.85, respectively). Conclusions: Depression screening rates among individuals with diabetes and no history of MDD were remarkably low. Patients with diabetes but no MDD diagnosis who sought health care at a FQHC clinic had more depressive symptoms than those with a history of MDD at both sites. Individuals with diabetes and who have a MDD diagnosis are much more likely to receive regular depression screening than those without MDD, which leaves a substantial proportion of patients with undetected depression. Depression screening must be enhanced for all individuals with diabetes, particularly for low-income individuals and those without a previous diagnosis of MDD.